Effects of progressive muscle relaxation exercises on patients with epilepsy on level of depression, quality of sleep, and quality of life: A randomized controlled trial - Talo, Beyan; Turan, Gulcan Bahcecioglu (W B Saunders Co Ltd, 2023)
Objective: This study aims to evaluate the effects of progressive relaxation exercises applied to patients with epilepsy on patients' depressive symptom severity, quality of sleep, and quality of life.Methods: The study was designed as a randomized controlled interventional study with a control group and pre-and post-test intervention. It was conducted with 70 patients with epilepsy, 35 in the intervention group and 35 in the control group, between November 1, 2021, and April 15, 2022. The patients in the intervention group were required to perform 12 progressive muscle relaxation exercise sessions 3 days a week for a total of 4 weeks. No interventions were made in the control group during the study. The data were collected with a Personal In-formation Form, Pittsburgh Sleep Quality Index (PSQI), Beck Depression Inventory (BDI), and Quality of Life in Epilepsy Inventory (QUOLIE-31).Results: The mean PSQI total score, subscale scores, and mean BDI total scores of the patients in the intervention group decreased significantly compared to those in the control group after the intervention (p<0.05). Addi-tionally, a significant difference was found between the mean QUOLIE-31 total scores and subscale scores of the patients in the intervention and control group after the intervention (p<0.05), the mean scores of the inter-vention group were significantly higher than those of the control group (p<0.05).Conclusion: Progressive muscle relaxation exercises decreased depressive symptoms severity and improved sleep and life quality in patients with epilepsy. Progressive relaxation exercises may be recommended as a comple-mentary nursing intervention in treating epilepsy.
Keywords: Depression; Epilepsy; Progressive muscle relaxation exercises; Sleep; Quality of life